Association between body composition, physical activity level and Illinois agility test performance in young males and females - Erdem Subak; Kaan Kaya; Şaban O. Viga; Muhammed H. Ocak; Ceren Ağaoğlu; Aslı Bekiroğlu (Physical Education of Students)
Background and Study Aim. Agility performance, which is a skill related to fast change of direction, explosiveness, and quickness, is a vital performance component for team sports. Illuminating factors that affect agility is substantial to understand the ability requirements and improve. This study aims to investigate correlations of the body analyze parameters and agility performance.